Simulation of Subsurface Drainage in the Sugarcane Crop under Different Spacing and Drain Depths - Rares Halbac-Cotoara-Zamfir; Asdrubal Jesus Farias-Ramirez; Jarbas Honorio de Miranda; Maria Alejandra Moreno-Pizani; Sergio Nascimento Duarte; Franklin Javier Paredes-Trejo; Luca Salvati; Cristina Halbac-Cotoara-Zamfir (Land, 2022)
Agricultural land drainage is an instrument for growing production and a tool for the conservation of land resources. The performance of land drainage systems is thus critical for achieving sustainable agricultural production Recently, many types of software have been developed in this field for modeling and simulating the performance of these systems. SISDRENA is a simulation model of the performance of underground drainage systems. The main objectives of this paper are to simulate different combination of depths and spaces between drains and to analyze their impact on potential sugarcane productivity in the western plains of Venezuela using a land drainage system model. Therefore, three climatic scenarios were defined by annual precipitation: dry years (25% below average), normal (mean) and humid (75% above average). The scenarios were implemented in three different soil types: sandy loam, loam and silt loam, with a hydraulic conductivity of 0.19, 0.26 and 0.04 m day−1, respectively. The simulation of the yield related to soil deficit (YRD) and water stress (YRW) indicated that the highest yields were reached for the larger spacing between drains and the high conductivity hydraulic of soils. In relation to the average relative productivity (YT), it was shown that in soils with a greater water retention capacity there is an inversely proportional relationship between the spacing between drains and the productivity. We concluded that in order to reach the maximum sugarcane yield, the effect of hydraulic conductivity is more important than the changes in the precipitation pattern.